Incorporating Quantitative Kinematic Gait and Balance Measurements into the Evaluation of Parkinson's Disease and Normal Pressure Hydrocephalus Patients. (16th November 2020) - Daly, Samuel; Hanson, Jacob; McGovern, Robert A
Abstract: INTRODUCTION: Movement disorder patients are typically evaluated with semi-quantitative rating scales. While clinically useful for characterizing the global disease burden, these measures may obscure important nuances. We've begun incorporating quantitative movement analysis into the pre-surgical evaluation of movement disorder patients, specifically for gait and postural instability. While NPH classically presents with "magnetic gait, " it can be difficult to distinguish between PD and NPH in the absence of PD-specific signs. METHODS: Patients with PD and NPH, undergoing work-up for neurosurgical intervention, were included. Quantitative gait and balance testing were conducted with and without treatment (PD: ON and OFF medication states; NPH: at baseline and following lumbar drain trial (LDT). Gait was assessed by measuring stride length and stride velocity with inertial measurement units (IMUs, XSens, Enshede, Netherlands). Balance was assessed with repeated pull tests, which were quantified with IMU measurements of the acceleration of the center of mass (ACOM) and reactive step length (RSL). Linear regression was used to calculate a slope and intercept for the relationship between ACOM and RSL. The averages of the measures between disease states were compared with t-tests. RESULTS: Eleven PD patients (10M) and eight NPH patients (8M) were included in the study. NPH patients were significantly older (73+/−2.8 vs. 62+/−2.3 years, p<.0053) and had significantly higher baseline UPDRS gait and pull test scores (2.38+/−.29 vs. 1.18+/−.25, p = .006; 1.63+/−.322 vs. 0.46+/−.27, P  = .013). Prior to appropriate treatment, gait measures were significantly worse in NPH patients than PD patients (stride length: 0.56+/−.09 vs. 1.03+/−.08 m, p = .001; stride velocity: 1.77+/−.16 vs. 2.96+/−.14 m/s, p<.0001, respectively), but balance measures (slope and intercept of ACOM vs. RSL) were no different. This relationship between disease states was also true following appropriate treatment. CONCLUSION: Quantitative movement analysis can easily be incorporated into the presurgical evaluation of movement disorder patients. Interestingly, while NPH patients had significantly worse gait findings, postural instability was similar between the two disease states. Future work will focus on using pre-operative improvement in these parameters to predict post-operative improvement and optimize patient selection.